Composition and distribution of bacterial communities and antibiotic resistance genes in fish of four mariculture systems. (15th October 2022) - Zhang, Mingqing; Hou, Liping; Zhu, Yating; Zhang, Cuiping; Li, Wen; Lai, Xingxing; Yang, Jinlin; Li, Shuisheng; Shu, Hu
Abstract: Fish-related antibiotic resistance genes (ARGs) have attracted attention for their potentially harmful effects on food safety and human health through the food chain transfer. However, the potential factors affecting these ARGs have not been fully explored. In this study, ARGs and bacterial communities in the fish gut, mucosal skin, and gill filaments in fish were comprehensively evaluated in four different mariculture systems formed by hybrid grouper ( Epinephelus fuscoguttatus ♀ ×  E. lanceolatus ♂), Gracilaria bailinae, and Litopenaeus vannamei using different combinations. The results showed that 9 ARGs were detected in the gut and mucosal skin and 6 ARGs in the gill filaments. The detection rate of aphA1 was the highest, and the abundance was 1.91 × 10 −3 - 6.30 × 10 −2 copies per 16 S rRNA gene. Transposase gene ( tnpA-04 ) was detected in all samples with the abundance of 3.57 × 10 −3 - 3.59 × 10 −2 copies per 16 S rRNA gene, and was strongly correlated with multiple ARGs (e.g., aphA1, tet(34), mphA-02 ). Proteobacteria, Deinococcus-Thermus, Firmicutes, and Bacteroidetes were the dominant phyla in the four mariculture systems, accounting for 65.1%–96.2% of the total bacterial community. Notably, the high relative abundance of Stenotrophomonas, a potential human pathogen, was elevated by 20.5% in the hybrid grouper gut in the monoculture system. In addition, variation partitioning analysis (VPA) showed that the difference in bacterial communities between mariculture systems was the main driving factor of ARGs distribution differences in hybrid groupers. This study provides a new comprehensive understanding of the characterization of fish-related ARGs contamination in different mariculture systems and facilitates the assessment of potential risks of ARGs and pathogen taxa to human health. Graphical abstract: Image 1 Highlights: The mucosal skin and gill in IMTA systems had higher ARGs abundance. High abundance of the pathogen Stenotrophomonas in grouper monoculture system. Bacterial differences between aquaculture systems drove ARGs differences. AphA1 / tnpA-04 result suggests aminoglycoside resistance/transmission risk. IMTA of fish-algae is a recommended production method for groupers.